Why Does a Mature Volcano Need New Vents? The Case of the New Southeast Crater at Etna - Acocella, Valerio; Neri, Marco; Behncke, Boris; Bonforte, Alessandro; Del Negro, Ciro; Ganci, Gaetana (Frontiers in Earth Science, 2016)
Mature volcanoes usually erupt from a persistent summit crater. Permanent shifts in vent location are expected to occur after significant structural variations and are seldom documented. Here we provide such an example that recently occurred at Etna. Eruptive activity at Mount Etna during 2007 focused at the Southeast Crater (SEC), the youngest (formed in 1971) and most active of the four summit craters, and consisted of six paroxysmal episodes. The related erupted volumes, determined by field-based measurements and radiant heat flux curves measured by satellite, totalled 8.67 x 106 m3. The first four episodes occurred, between late-March and early-May, from the summit of the SEC and short fissures on its flanks. The last two episodes occurred, in September and November, from a new vent (“pit crater” or “proto-NSEC”) at the SE base of the SEC cone; this marked the definitive demise of the old SEC and the shift to the new vent. The latter, fed by NW-SE striking dikes propagating from the SEC conduit, formed since early 2011 an independent cone (the New Southeast Crater, or “NSEC”) at the base of the SEC. Detailed geodetic reconstruction and structural field observations allow defining the surface deformation pattern of Mount Etna in the last decade. These suggest that the NSEC developed under the NE-SW trending tensile stresses on the volcano summit promoted by accelerated instability of the NE flank of the volcano during inflation periods. The development of the NSEC is not only important from a structural point of view, as its formation may also lead to an increase in volcanic hazard. The case of the NSEC at Etna here reported shows how flank instability may control the distribution and impact of volcanism, including the prolonged shift of the summit vent activity in a mature volcano.